Developing Blended Learning-Based Syllabus of English for Pharmacy; Students' Needs Analysis - Faisal Rahman; Rohama (JELLT (Journal of English Language and Language Teaching), 2022)
English is an obligatory course for pharmacy students at Sari Mulia University. However, the syllabus utilized in the course has not yet been developed based on the students’ needs. This research aims to identify students’ target and learning needs to develop a syllabus of English for pharmacy. The research method employed in this research is Research & Development (R & D), consisting of the five steps mentioned analysis, design, development, implementation, and evaluation (ADDIE). This article explores the result of the first step which needs analysis. Various studies have developed syllabi for pharmacy students. Nevertheless, this study conducts a blended-learning-based syllabus. The data were collected using a questionnaire to obtain the students’ target and learning needs of English for pharmacy. The participants were 101 students of the pharmacy study program at Sari Mulia University who will take an English course in the upcoming semester. The sample was selected using a simple random technique. The finding indicated that the students’ most expected target in learning English is to improve their confidence in communication. Besides, they also expected to be able to master basic English skills, basic English grammar, and vocabulary related to pharmacy. The learning method that the students preferred was teacher-centered learning, where the teacher explains more than the students’ individual activity; however, they also expected to learn in group or pair activity. The usage of technology for blended learning that is expected by most of the students is watching videos; meanwhile, the least expected is learning via LMS.